Peran Magang Microteaching dalam Meningkatkan Kompetensi Guru dalam Mengajar Keterampilan Dasar pada Pendidikan Islam Anak Usia Dini - Alia Rohali; Cut Nurul Haniyah; Fauziah Nasution; Mastianur Daulay; Nurlaila Hayati (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
One of the efforts to increase the ability to teach masterfully is through microteaching which is carried out to maintain the quality of teaching ability, learning performance and also a good and structured learning experience. With qualified teaching skills that affect classroom management skills as well as increasing learning outcomes according to standards, it is expected to increase competitiveness through human resources that are able to turn challenges into repeaters. The aim of research is the development of microtelaching asselmel learning as an effort to prepare prospective graduates with qualified skills and teaching experience in the future for gurus through improving teaching skills. Online microtelaching as an effort to prepare professional and qualified academic candidates during the Covid-19 pandemic was designed and implemented in the learning process in microtelaching courses. Kelyword : Microtelaching, competency